Design, synthesis and biological evaluation of novel 1-methyl-3-oxo-2, 3, 5, 6, 7, 8-hexahydroisoquinolins as potential EZH2 inhibitors. Issue 33 (12th April 2015) - Zhang, Lidan; Song, Xuejiao; Wang, Ningyu; Zhao, Lifeng; Feng, Qiang; You, Xinyu; Peng, Cuiting; Gao, Tiantao; Xiong, Menghua; He, Bing; Gao, Chao; Luo, Yong; et al.
<x xml:space="preserve">Abstract</x> This study led to the discovery of several potent compounds with low nanomolar to sub-nanomolar potency for EZH2.